Analyses of time-related performance of betavoltaic batteries using TiT2. (20th August 2020) - Li, Xiaoyi; Lu, Jingbin; Zheng, Renzhou; Wang, Yu; Xu, Xu; Liu, Yumin
Abstract: The time effect of tritium silicon p–n junction betavoltaic batteries is considered in this work. For a titanium tritium (TiT2 ) source, the processes of decaying, tritium leaking, swelling and 3 He releasing are contained in the calculation, and expressions of component and density changes are obtained. As time goes by, the self-absorption rate has a downward trend, while all electrical performances decrease, especially the short-circuit current ( ISC ) and the maximum output power ( Pmax ). At about 3.5 a, the battery begins to release gaseous 3 He, and the expiry date of the battery is about 10.7 a, shorter than the half-life of tritium. The result indicated that for a tritium source, the time leads to a significant reduction in the electrical performance of the battery, which cannot be ignored in simulations and experiments.